2014
DOI: 10.1007/s11136-014-0651-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the eight-item modified Medical Outcomes Study Social Support Survey based on Spanish outpatients

Abstract: Psychometric properties of the Spanish version of the mMOS-SS in outpatients attending a PHCS are adequate. Factor analysis confirmed a one-factor model with acceptable fit indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 17 publications
1
39
0
2
Order By: Relevance
“…It also shows the same moderate correlations with indicators of health and social connectedness as the 19-item measure, supporting this conclusion. These findings are consistent with other validation studies of abbreviated versions of the MOS-SSS [2,5,7]. All three studies reported satisfactory goodness-of-fit statistics for their abbreviated total score.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It also shows the same moderate correlations with indicators of health and social connectedness as the 19-item measure, supporting this conclusion. These findings are consistent with other validation studies of abbreviated versions of the MOS-SSS [2,5,7]. All three studies reported satisfactory goodness-of-fit statistics for their abbreviated total score.…”
Section: Discussionsupporting
confidence: 89%
“…However, there were differences in the items included in these abbreviated measures. This study and the one by Gjesfeld [2] selected items based on factor structure derived from previous studies, whereas the other two studies selected the first eight items listed, which are predominantly 'tangible support' items [5,7]. Despite these differences, all studies found satisfactory model fit for their abbreviated 1-factor measures.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A number of subsequent studies have also been mostly done on medically ill patients, e.g. American breast cancer patients [17] or Spanish outpatients from a primary care center [18]. Given its easy comprehensibility with a single sentence stem “If you needed it, how often is someone available…”, the instrument lends itself to use in a wide range of populations and age groups.…”
Section: Introductionmentioning
confidence: 99%